Colombia : Third Review Under the Extended Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper examines the Third Review Under the Extended Arrangement for Colombia. Considerable macroeconomic stabilization has been achieved under the program. Inflation has been reduced, fiscal consolidation has advanced, the exchange market has remained orderly, and significant structural reforms have been implemented, albeit with some slippages. The 2002 program calls for a reduction in inflation to 6 percent, maintenance of a strong external position, and a further strengthening of the public finances to gain better control over the public debt dynamics and help lay the ground for a robust recovery of activity in the private sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet